2020
DOI: 10.2224/sbp.9014
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and employee innovative behavior: The mediating role of employee voice

Abstract: We examined employee voice as the mediator in the social media use–employee innovative behavior relationship in the current Web 2.0 age. We used structural equation modeling to test this mediating role with 178 employees of a large enterprise in China. The results showed a significant positive relationship between social media use and employee voice, and between employee voice and innovative behavior, and a positive but not significant relationship between social media use and employee innovative behavior. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The hypothesis testing results showed that social media usage had a positive and significant effect on the innovative work behavior. It aligned with previous empirical study conducted by Han and Xia (2020), which showed that social media usage positively and significantly affected innovative work behavior. In addition, the research by Saleem et al (2017) also showed a significant positive relationship between social media usage and innovative behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The hypothesis testing results showed that social media usage had a positive and significant effect on the innovative work behavior. It aligned with previous empirical study conducted by Han and Xia (2020), which showed that social media usage positively and significantly affected innovative work behavior. In addition, the research by Saleem et al (2017) also showed a significant positive relationship between social media usage and innovative behavior.…”
Section: Discussionsupporting
confidence: 90%
“…The study also stated that social media usage for innovative behavior research was due to their inability to cull large amounts of data, most of which was “noise.” Thus, organizations warn to rely on something other than the number and word cloud as this leads to general ideas while it will miss out on innovative things (Raman & Menon, 2018). Empirical research conducted by Han and Xia (2020) has shown that social media usage positively and significantly affects innovative work behavior. In addition, Saleem et al (2017) research shows a significant positive relationship between social media usage and innovative behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are other mediating variables. For example, Han and Xia [ 115 ] found the mediating role of employee voice for employee innovation. Cheng and Cho [ 84 ] found the mediating role of work break activities for employee recovery experience.…”
Section: Discussionmentioning
confidence: 99%
“…cognition) have positive effects on employee performance in creative and innovative tasks. Moreover, some studies found that the positive relationship between ESM usage and employee innovative performance is mediated by some variables, such as the connection between teams (Kuegler et al, 2015), work engagement (Cheng et al, 2020) and employee voice (Han and Xia, 2020). 4.4.3.2.3 .…”
Section: Analysis Of Landmark Research In the Esm Literaturementioning
confidence: 99%